A low temperature gradual annealing scheme for achieving high performance perovskite solar cells with no hysteresis. Issue 27 (22nd June 2015) - Xu, Mei-Feng; Zhang, Hong; Zhang, Su; Zhu, Hugh L.; Su, Hui-Min; Liu, Jian; Wong, Kam Sing; Liao, Liang-Sheng; Choy, Wallace C. H.
Abstract : A facile low temperature gradual annealing scheme has been developed to tune the amount of chlorine in perovskite film. Abstract : CH3 NH3 PbI3 is commonly used in perovskite solar cells due to its long diffusion length and good crystallinity. In this paper, in the one-step approach using CH3 NH3 I and PbCl2 for forming the perovskite, we present a new low temperature annealing approach of gradually increasing the temperature to fabricate perovskite films. Various temperatures and temperature ranges for the formation of perovskite films have been studied. Using the gradual annealing process, we can tune the amount of chlorine in the atomic ratio of chlorine/iodine from 1.2 to 4.0%. Meanwhile, the gradual annealing process influences the quality of the perovskite film and importantly the device performance. The results show that through the optimized process, the film quality is improved with high surface coverage and good photoluminescence and reproducibility. We find that a higher amount of chlorine in the perovskite film plays a positive role in the device performance in the approach for achieving a power conversion efficiency of 14.9% with no obvious hysteresis.